Efektivitas Metode Steinberg Dengan Media Big Book Terhadap Membaca Pemahaman Di Kelas Iii Sekolah Dasar - Susi Liasambu; Kasmawati Kasmawati; La Sisi (Prodi PGSD Unsultra, 2021)
This study was motivated by the low reading comprehension ability of students. The purpose of this study was to describe the effectiveness of the Steinberg method using Big Book media on reading comprehension. The research method used was a quasi-experimental design with a pretest–posttest involving two groups: an experimental class and a control class. The experimental class received treatment using the Steinberg method with Big Book media, while the control class used conventional methods. The results showed a significant difference in reading comprehension between the two classes. The control class, which used conventional methods, showed no significant improvement, whereas the experimental class experienced a notable increase in reading comprehension. Based on data analysis, the average pretest score of the experimental class was 42, which increased to 75 after treatment—an improvement of 33 points. These results indicate that the Steinberg method assisted by Big Book media is effective in improving students’ reading comprehension.